Meningeal Ewing Sarcoma/Peripheral PNET: Clinicopathological, Immunohistochemical and FISH study of four cases. Issue 1 (8th August 2016) - (柯昌庶), Changshu Ke; (段秋红), Qiuhong Duan; Yang, Hui; Zhu, Feng; Yan, Meng; Xu, San‐peng; Zhou, Sheng; Wan, Feng; Shu, Kai; Lei, Ting; Xia, Li‐ming
Abstract : Meningeal Ewing Sarcoma (ES)/peripheral primitive neuroectodermal tumor (pPNET) is a rare diagnostically challenging small round cell tumor in the CNS. This study investigates the clinical pathological features of four cases of this tumor from archives of 6 years in our hospital. Patients were within the median age of 21.5 years and male to female ratio was 1:1. The tumors distributed at the supra‐tentorial location, posterior fossa and lumbar vertebral canal, usually presenting as the dura‐sited nodule or having close connection with the meninges within the cranium or vertebral canal. Histopathologically, small round undifferentiated tumor cells with hypercellularities, scant cytoplasm and inconspicuous nucleoli were observed, although some components such as atypical larger vesicular nuclei, prominent nucleoli of tumor cells, necrotic foci and mesenchymal collagen proliferation forming the lobular structure, were also appreciated. Immunohistochemally, tumor cells displayed membranous positivity of CD99 (4/4), nuclear positivity of FLI‐1 (4/4) and NKX2.2 (4/4), negativity of EMA, GFAP and synaptophysin expression. The histochemical PAS staining showed weak positivity in one case. Fluorescence in situ hybridization (FISH) test using EWSR1 (22q12) dual color break apart rearrangement probe showed positive results in two cases. Results suggest that using a panel of immunohistochemical markers, including NKX2.2, CD99, FLI‐1, EMA, GFAP and synaptophysin, combined with the supplementary EWSR1 FISH test, helps to define the diagnosis of meningeal ES/pPNET of CNS.